Does Culinary Nostalgia Shape Touristic Behaviour? - Lavinia Denisia Cuc; Mioara Florina Pantea; Dana Rad; Vanina Adoriana Trifan; Ioan Codruț Țurlea (Amfiteatru Economic, 2024)
This study explores the influence of culinary nostalgia on tourist behaviour, offering a detailed analysis of how this psychological factor, combined with others, shapes tourists' preferences. The research employs quantitative methods, relying on network analysis applied to data collected from a sample of 535 participants. The results demonstrate that culinary nostalgia plays a significant role in triggering memories related to past food experiences and cultural heritage, directly influencing travel decisions. Additionally, the study highlights that the perception of service quality contributes to increasing tourist engagement in culinary tourism through a complex mechanism mediated by three factors: culinary attractor, culinary nostalgia, and culinary socialisation. These complex interactions between service quality and psychological factors influence tourist participation, offering new perspectives on how tourist destinations can leverage nostalgia and service quality to promote sustainable and cultural tourism. These results indicate that adopting a nostalgic-cultural strategy, together with offering top-notch services, can greatly improve tourist experiences and promote sustainability in culinary tourism. Therefore, this study enhances the existing body of knowledge by emphasising the need to include emotional aspects and improvement of service quality in strategies for developing tourism.